Variability of salivary analytes under daily conditions and their implications for periodontitis biomarkers - Amanda Carolina Souza Delfino Rocha; Renata Klemp Orlandini; Ana Carolina Fragoso Motta; Juliana Barchelli Pinheiro; Gilberto André e Silva; Viviane de Cássia Oliveira; Alan Grupioni Lourenço (Frontiers Media S.A., 2024)
IntroductionRecent studies have identified inflammatory mediators as potential biomarkers for monitoring or diagnosing periodontitis. However, the brief half-life of these mediators, coupled with their variability among different individuals and across different stages of periodontal disease, may limit their reliability as biomarkers.MethodsIn this study, we assessed the concentration profile of salivary biomarkers (IL-6, IL-8, and total protein) through repeated measurements within the same day and across different days in 79 patients exhibiting various states of periodontal health: intact periodontium, stable periodontitis, and active periodontitis. Additionally, we explored how daily variations, such as the interval between toothbrushing and eating, impact the levels of these salivary biomarkers and their diagnostic efficacy for periodontitis activity.ResultsOur results showed high salivary levels of IL-6 and total proteins in periodontitis patients (p < 0.001), with detection ability reflected by an Area Under the Receiver Operating Characteristic Curve (AUC-ROC) ranging between 0.709 and 0.852. Conversely, IL-8 levels were higher in patients with intact periodontium (p < 0.001), with an AUC-ROC for periodontitis detection between 0.671 and 0.815. Daily activities such as toothbrushing and eating influenced the levels of specific analytes, particularly total proteins (p < 0.001), but this did not affect their ability to detect periodontal disease activity. The highest measurement agreement, assessed by Intraclass Correlation Coefficients (ICC), was found for IL-6, with no significant differences in agreement between same-day and different-day measurements.ConclusionsOur study demonstrated consistency in the repeated measurements of salivary analytes, both within the same day and across different days, except for salivary total protein levels. These analytes exhibited variability within a range that did not undermine their effectiveness as biomarkers for periodontal disease.